2015
DOI: 10.1007/s11999-015-4462-z
|View full text |Cite
|
Sign up to set email alerts
|

Cemented Bipolar Hemiarthroplasty Provides Definitive Treatment for Femoral Neck Fractures at 20 Years and Beyond

Abstract: Background Displaced femoral neck fractures frequently are treated with bipolar hemiarthroplasties. Despite the frequency with which bipolar hemiarthroplasty is used to treat these fractures, there are few long-term data. Questions/purposes We sought to evaluate (1) the cumulative incidence of revision for any reason of bipolar hemiarthroplasties at 20 years, and the proportion of patients who lived more than 20 years who still have the prosthesis in situ from the index arthroplasty, (2) the cumulative inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In THA, the femoral stem should be selected according to patient's diagnosis, BMD and shape of the femur. The use of a cemented stem allows early ambulation by obtaining initial firm fixation 12 13 14) . However, cardiovascular complications have been associated with this approach (e.g., intraoperative fat embolism, bone cement embolism, vasodilation due to autonomic reflex); additionally, failure of biologic fixation, thigh pain, stress-shielding, bone resorption and loosening, and difficulty of stem extraction in revision surgery have been reported at both mid- and long-term follow-up 15 16) .…”
Section: Discussionmentioning
confidence: 99%
“…In THA, the femoral stem should be selected according to patient's diagnosis, BMD and shape of the femur. The use of a cemented stem allows early ambulation by obtaining initial firm fixation 12 13 14) . However, cardiovascular complications have been associated with this approach (e.g., intraoperative fat embolism, bone cement embolism, vasodilation due to autonomic reflex); additionally, failure of biologic fixation, thigh pain, stress-shielding, bone resorption and loosening, and difficulty of stem extraction in revision surgery have been reported at both mid- and long-term follow-up 15 16) .…”
Section: Discussionmentioning
confidence: 99%
“…analyzed 376 cemented bipolar HAs and found that the rate of conversion to THA at 20 years was only 3.5% and that only 1.4% were due to cartilage wear 47 . Even though an increase in patient age is commensurate with decreased activity level and thus decreased cumulative wear over time, no living patient at the endpoint of follow-up showed cartilage wear or implant loosening 47 . In the most recent meta-analysis, Jia et al .…”
Section: Unipolar Vs Bipolar Hemiarthroplastymentioning
confidence: 99%
“…Hemiarthroplasty and total hip arthroplasty have both been well described as effective methods of management for displaced femoral neck fractures in the elderly [15]. Total hip arthroplasty has superior functional outcomes and lower long-term revision rates [69], while hemiarthroplasty is associated with lower dislocation rates and faster operative times.…”
Section: Introductionmentioning
confidence: 99%